Elaboration and Use of Communication Media in Teaching and Learning The Arabic Language for Foreigners | اندماج وسائل الاتصال واستخدامه في تعليم وتعلم اللغة العربية للناطقين بغيرها - Ahmed Safidin (Al-Zahra: Journal for Islamic and Arabic Studies)
This paper addresses the issue of teaching and learning the Arabic language for non-native speakers through its focus on an integrated vision of the means of communication. Through the descriptive method the process of employing communication techniques in teaching and learning the Arabic language for non-native speakers through three topics. The first topic deals with teaching and learning the Arabic language for non-native speakers, and the second topic deals with the employment and use of communication methods in this matter, and the third topic is a vision on strengthening the relationship between Sudan and the Republic of Indonesia, through the establishment of a Sudanese Center for Distance Education to spread the Arabic language and Islamic sciences.